Neoplasm of the large bowel fistulized in the caecum. - Cresseri, Aída; Estapé, Gonzalo; Scigliano, Héctor (Cirugía del Uruguay, 1988)
A neoplasm of the tranverse right large bowel fistuli• zed in the caecum is presentad. This anatomical variety of tumor is of low rate in both national and foreign serles. At five months a second look was performed with• out flnding residual tumor, with good evolution until present.